PROGRAM LEGISLASI DAERAH (PROLEGDA) SEBAGAI INSTRUMEN PERENCANAAN PEMBENTUKAN PERATURAN DAERAH (Studi Atas Pelaksanaan Prolegda di Provinsi Nusa Tenggara Timur) - , YORDANUS HOGA DATON ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study is to analyze and evaluate in order to know the proportion of the materialâs content as the basic of determination of the plan of the regional regulations through the legislation program and to know the public participation in the organization of the regional legislation program in the province of Nusa Tenggara Timur. This study is empirically normative combining empirical legal research with normative legal research which is used as needed, with direct interviews. The data which has been compiled systematically be analyzed using qualitative descriptive methods. The result of the study show that the regional policy legislation in the province of Nusa Tenggara Timur has not ladled out regulatory authority or substance proportionately which becomes domain of regulatory arrangements between the local regulatory authority or substance with another substance. Regional policy legislation in three locations of the study shows a very high propensity to implement the regulations which is higher than the substance of regulatory authority or other local regulations. The imbalance between the proportionâs regulatory or the subject between one to another is caused by a number of factors such as the strength of the positive paradigm and the centralism of law in the national law system as well as institutional and political factors and also technical legislation of the regional government or DPRD as the executant of regional legislative function. Although the establishment of regional legislation program at both the Provincial Governments of East Nusa Tenggara and East Flores regency no room for public participation or lack of documents on the Government legislation program Kupang district, but in the legislative process stages and there is still open space areas for public participation by RDPU, Working visits and socialization is limited to some local regulations. Even at three study sites are local regulations initiated by the design community. Public participation was implemented involving limited by only including bureaucratic elite in the District / Municipal and District and Village.